Chief of Mbiseniku, Bikom District Bamenda Division (Colonial Letters and the Contact of Knowledges, 1926)
This file contains colonial memoranda and petition by Chief of Mbiseniku, Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Chiefship; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies